Bridging Sacred Text and Language Pedagogy: Designing Quran Based Arabic Materials Through Pedagogical Grammar - Midyan Surya Ishak; Sabaruddin Garancang; Amrah Kasim; Marjuni Marjuni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Many learners of the Arabic language struggle to access primary Islamic sources, which are predominantly written in Arabic. Mastery of Quranic Arabic is essential in both Islamic studies and Arabic language acquisition, particularly for non-native speakers aiming to understand Islamic teachings. However, conventional methods of teaching Arabic grammar often focus heavily on theoretical aspects and fail to develop practical language skills. This study investigates the role of pedagogical grammar in Arabic language instruction, particularly in the development of teaching materials tailored to Quranic Arabic. Employing the 4D research and development model (Define, Design, Develop, Disseminate) by Thiagarajan, the study designed pedagogical grammar-based instructional materials using Quranic texts. These materials were tested on a cohort of 40 fourth-semester students. The findings demonstrate that instructional materials developed through a pedagogical grammar approach, incorporating authentic Quranic texts, significantly enhance learning outcomes. Students showed statistically significant improvement in performance, particularly in the qawāʿid li al-mutaqaddimīn course. The study concludes that pedagogical grammar-based materials are effective and should be further implemented in Islamic higher education institutions to enrich grammar instruction, optimize learning efficiency, and foster deeper engagement with Quranic texts.